Trigger Pulse Generator Using Proposed Buffered Delay Model and Its Application - Amit Krishna Dwivedi; Kumar Abhijeet Urma; Aminul Islam (Active and Passive Electronic Components)
This paper proposes a circuit capable of incorporating buffered delays in the order of picoseconds. To study our proposed circuit in the profound way, we have also explored our proposed circuit using emerging technologies such as FinFET and CNFET. Comparisons between these technologies have been made in terms of different parameters such as duration of incorporated delays (pulse width) and its variability with supply voltages. Further, this paper also proposes a trigger pulse generator by utilizing proposed buffered delay circuit as its basic element. Parametric results obtained for the proposed trigger pulse generator match different application specific requirements. These applications are also mentioned in this paper. The proposed trigger pulse generator requires very low supply voltage (700 mV) and also proves its effectiveness in terms of tunability of pulse width of the generated pulses. The modeling of the circuit has been done using Verilog and the simulation results are extensively verified using SPICE.